2019
DOI: 10.3906/sag-1804-173
|View full text |Cite
|
Sign up to set email alerts
|

miR-33 and RIP140 participate in LPS-induced acute lung injury

Abstract: Background/aim: Pulmonary microvascular endothelial cells (PMVECs) play a pivotal role in the process of acute lung injury (ALI), which can be induced by lipopolysaccharide (LPS). Numerous reports have indicated that both miR-33 and RIP140 are involved in the inflammatory response in macrophages. In this study, we sought to investigate whether miR-33 and RIP140 participate in ALI induced by LPS. Materials and methods: First, we isolated and identified PMVECs from BALB/c mice. Subsequently, both PMVECs and BALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…LPS or endotoxin is a proinflammatory cytokine with very high bioactivity. Li et al [ 22 ] found that LPS was able to directly act on PMVECs, induce the release of inflammatory factors, and lead to cell permeability change, cytoskeleton rearrangement, cell cycle arrest, and cell apoptosis. Currently, no radical measures have been found to directly prevent PMVECs from injury, and the research hotspots mainly focus on searching for suitable drugs to help PMVECs resist LPS-induced cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…LPS or endotoxin is a proinflammatory cytokine with very high bioactivity. Li et al [ 22 ] found that LPS was able to directly act on PMVECs, induce the release of inflammatory factors, and lead to cell permeability change, cytoskeleton rearrangement, cell cycle arrest, and cell apoptosis. Currently, no radical measures have been found to directly prevent PMVECs from injury, and the research hotspots mainly focus on searching for suitable drugs to help PMVECs resist LPS-induced cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. also showed that MiR-33 is involved in acute lung injury provoked by LPS, too ( Li et al., 2019 ). Moreover, over-expression of MiR-146b could alleviate ARDS, both in mice and in cells ( He et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data represent the average and standard deviation of three biological replicates. The SMS2 expression level was normalized to the expression of GAPDH [ 46 ].…”
Section: Methodsmentioning
confidence: 99%